Transamidation of secondary carboxamides and amidation of esters are facilitated by magnetic Co@NC nanoparticles, as a highly efficient and recyclable catalyst under neat conditions - Singh V.; Rajput K.; Mahaur P.; Singh S.; Srivastava V. (My University, 2025)
A novel and highly efficient technique has been demonstrated for the transamidation of N-tert-butoxycarbonyl (N-Boc) activated secondary amides, as well as the direct amidation of esters with amines, resulting in the formation of amide bonds. This technique exhibits exceptional selectivity in cleaving N-C/O-C bonds and utilizes Co@NC as a highly efficient magnetic nano-catalyst. The method stands out for its solvent-free conditions, environmentally friendly catalyst, straightforward work-up, and the ability to easily reclaim (aided by an external magnet) and reuse the catalyst for up to five cycles without significant loss of catalytic activity, showcasing both novelty and efficiency. © 2024 The Royal Society of Chemistry.